f(x) = -4x + 1
g(x) = 3x + 1
A. (f + g)(x) = (-4x + 1) + (3x + 1)
(f + g)(x) = (-4x + 3x) + (1 + 1)
(f + g)(x) = x + 2
Domain: (-∞, ∞) x ∈ R
B. (f - g)(x) = (-4x + 1) - (3x + 1)
(f - g)(x) = (-4x - 3x) + (1 - 1)
(f - g)(x) = -7x
Domain: (-∞, ∞) x
C. (f · g)(x) = (-4x + 1)(3x + 1)
(f · g)(x) = -4x(3x + 1) + 1(3x + 1)
(f · g)(x) = -4x(3x) - 4x(1) + 1(3x) + 1(1)
(f · g)(x) = -12x² - 4x + 3x + 1
(f · g)(x) = -12x² - x + 1
Domain: (-∞, ∞) x ∈ R
D. (f ÷ g)(x) = (-4x + 1) ÷ (3x + 1)
Domain: (-∞, ⁻¹/₃) U (⁻¹/₃, ∞) x